Answer:
Step-by-step explanation:
To solve this equation, isolate it on one side of the equation.
Use the distributive property.
Distributive property:
⇒ A(B+C)=AB+AC
⇒ A(B-C)=AB-AC
4(x+1)=-16
First, divide by 4 from both sides.
[tex]\Longrightarrow: \sf{\dfrac{4\left(x+1\right)}{4}=\dfrac{-16}{4}}[/tex]
Solve.
Divide these numbers goes from left to right.
-16/4=-4
[tex]\Longrightarrow: \sf{x+1=-4}[/tex]
Subtract by 1 from both sides.
[tex]\sf{x+1-1=-4-1}[/tex]
Solve.
-4-1=-5
[tex]\Longrightarrow: \boxed{\sf{x=-5}}[/tex]
I hope this helps, let me know if you have any questions.